Fuzzy Logic Controller Based Single Buck Boost Converter for Solar PV Cell - Krishnan Manickavasagam (Institute of Advanced Engineering and Science, 2014)
This paper deals with solar power production controlled by Fuzzy Logic Controller (FLC) and Single Input Buck-Boost (SIBB) converter. Since the solar energy is continuously varying, according to the irradiation the FLC generates control pulses to switch on the MOSFET device. To analyze the real time feasibility of this method, the system is simulated by using MATLAB/Simulink 2010a. A simulation model of the system is developed with solar Photovoltaic (PV) cell, FLC and SIBB in contradiction of the real world conditions. The results are presented and discussed in this paper.